1999
DOI: 10.1007/s004050050125
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral facial nerve schwannomas

Abstract: Facial nerve schwannoma is an uncommon tumor and bilateral facial nerve tumors are extremely rare. A case is presented in which neuromas affecting the intra-canalicular and labyrinthine portions of both facial nerves occurred. Radiologic assessment demonstrated the origin of these tumors. Eventual tumor involvement of the sole functioning cochlea resulted in the development of total hearing loss. Management entailed symptomatic care and surgical resection. Auditory rehabilitation was attempted using cochlear i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 9 publications
1
8
0
2
Order By: Relevance
“…Although the estimate prevalence is extremely low (1), FNS are the most common primary tumor of the facial nerve (FN) (2). No clear treatment consensus has been developed because of the infrequent presentation of these slow-growing benign tumors.…”
mentioning
confidence: 99%
“…Although the estimate prevalence is extremely low (1), FNS are the most common primary tumor of the facial nerve (FN) (2). No clear treatment consensus has been developed because of the infrequent presentation of these slow-growing benign tumors.…”
mentioning
confidence: 99%
“…23 There are isolated reports of dissecting the tumor from the nerve and obtaining normal or adequate functional outcomes. 2,9,24,25 In our Case 2, the facial trunk was preserved. The facial nerve was easily identifed because the tumor originated from the chorda tympani.…”
Section: Discussionmentioning
confidence: 56%
“…He used the MCF approach combined with the transmastoid approach for many of the patients in his original series. Other series have reported the combined approach as well 3,8,12 . However, MCF alone for tumor debulking has been sparsely reported in the literature 3,12 .…”
Section: Discussionmentioning
confidence: 99%
“…Other series have reported the combined approach as well 3,8,12 . However, MCF alone for tumor debulking has been sparsely reported in the literature 3,12 . Sherman et al reported on a series of patients in which only one patient had a subtemporal approach for tumor debulking.…”
Section: Discussionmentioning
confidence: 99%